Nucleotide substitutions within the cardiac troponin T alternative exon disrupt pre-mRNA alternative splicing. - Cooper, T A (1989)
The cardiac troponin T (cTNT) pre-mRNA contains a single alternative exon (exon 5) which is either included or excluded from the processed mRNA. Using transient transfection of cTNT minigenes, we have previously localized pre-mRNA cis elements required for exon 5 alternative splicing to three small regions of the pre-mRNA which include exons 4, 5, and 6. In the present study, nucleotide substitutions were introduced into the region containing exon 5 to begin to define specific nucleotides required for exon 5 alternative splicing. A mutation within the 5' splice site flanking the cTNT alternative exon that increases its homology to the consensus sequence improves splicing efficiency and leads to increased levels of mRNAs that include the alternative exon. Surprisingly, substitution of as few as four nucleotides within the alternative exon disrupts cTNT pre-mRNA alternative splicing and prevents recognition of exon 5 as a bona fide exon. These results establish that the cTNT alternative exon contains information in cis that is required for its recognition by the splicing machinery.